Shh‐Yap signaling controls hepatic ductular reactions in CCl4‐induced liver injury. Issue 2 (30th September 2020) - Jin, Lifang; Huang, Huarong; Ni, Jian; Shen, Jiayuan; Liu, Zuping; Li, Lijing; Fu, Shengmin; Yan, Junyan; Hu, Baowei
Abstract: Carbon tetrachloride (CCl4 ) exposure can induce hepatic ductular reactions. To date, however, the related mechanism remains largely unknown. Sonic hedgehog (Shh) and Yes‐associated protein (Yap) signaling are correlated with liver injury and regeneration. Herein, we investigated the role of Shh and Yap signaling in the fate of ductular reaction cells in CCl4 ‐treated livers and the possible mechanisms. Wild‐type and Shh‐EGFP‐Cre male mice were exposed to CCl4 (2 mL/kg), and then treated with or without the Shh signaling inhibitor Gant61. The level of liver injury, proliferation of ductular reaction cells, and expression levels of mRNA and protein related to the Shh and Yap signaling components were assessed. Results showed that CCl4 treatment induced liver injury and promoted activation and proliferation of ductular reaction cells. In addition, CCl4 induced the expression of Shh ligands in hepatocytes, accompanied by activation of Shh and Yap1 signaling in the liver. Furthermore, administration of Gant61 ameliorated liver regeneration, inhibited hepatic ductular reactions, and decreased Shh and Yap1 signaling activity. Thus, Shh‐Yap1 signaling appears to play an integral role in the proliferation of ductular reaction cells in CCl4 ‐induced liver injury. This study should improve our understanding of the mechanism of CCl4 ‐induced liver injury and ductular reactions and provide support for future investigations on liver disease therapy.